OBSERVASI PENGELOLAAN PERPUSTAKAAN DAERAH DI KABUPATEN NGAWI - Muhammad Johan Dicky Aji Susanto; Ramdan Ridho Saputra (Prosiding Konferensi Ilmiah Dasar, 2026)
This study aims to describe the management of a regional library in Ngawi Regency, including services, collections, facilities, and the use of technology. This research uses a qualitative approach with observation, interviews, and documentation techniques. The results show that library management has been running fairly well, especially in terms of basic services and facilities. However, there are still several obstacles such as limited updated collections, suboptimal use of technology, and low public interest in visiting. Therefore, service innovation and technology-based development are needed to improve the role of libraries as community literacy centers.